Expression of bone-regulatory proteins in human valve allografts. Issue 9 (31st January 2006) - Shetty, R; Pepin, A; Charest, A; Perron, J; Doyle, D; Voisine, P; Dagenais, F; Pibarot, P; Mathieu, P
Abstract : Objective: To test the hypothesis that valve allograft (VA) calcification results from an ossification process in which bone-regulatory proteins are expressed. Methods: 15 VA that were explanted at the time of surgery for dysfunction were studied. VA were analysed and compared with normal aortic valves (n  =  20). Results: All the VA (5 aortic, 10 pulmonary) exhibited heavy calcification and important fibrosis. Immunohistochemistry studies showed that the bone-specific transcription factor Cbfa-1 was expressed by stromal cells. Bone alkaline phosphatase was expressed in calcified regions. Immunostaining for α smooth muscle (α-SM) actin was increased in VA compared with normal valves and in 6 of the 15 valves formed cellular clusters close to the calcified nodules. In VA osteopontin and osteonectin were expressed by stromal cells, whereas osteocalcin was closely associated with the calcified regions. Furthermore, analysis of the bone-regulatory proteins that control bone resorption showed that receptor activator of nuclear factor κB ligand (RANKL), receptor activator of nuclear factor κB (RANK) and osteoprotegerin (OPG) were differentially expressed in calcified VA and normal valves. Normal valve leaflets expressed OPG, whereas OPG expression was absent or faint in calcified VA. RANKL and RANK were not detected in normal valves, whereas calcified VA expressed RANKL and RANK. Conclusion: These data suggest that calcification of VA results from an ossification process, which relies on tight control of bone-regulatory protein expression. The expression pattern of the RANKL/RANK/OPG system suggests that it may have a regulatory role not only in osteoclastogenesis but also in the calcification of human VA.